Dissatisfiers and demand of hotels with poor online rating / Ardiana Mazwa Raudah Amir Abdullah and Vloreen Nity Mathew - Amir Abdullah, Ardiana Mazwa Raudah; Mathew, Vloreen Nity (Universiti Teknologi MARA Cawangan Sarawak, 2018)
Hotel booking nowadays has been made easy with technology. Customers from all over the world have better advantage as reviews by previous customers assisting them in their final purchase decisions. Satisfied customers provide positive reviews while dissatisfied ones would share negative reviews on elements contributing to the unpleasant experience. As many other studies mainly focused on enhancing customers’ satisfactions, this research focuses on identifying the elements of dissatisfaction (or sometimes regarded as the dissatisfier). Generally, negative elements always have a greater impact on customers’ purchase intention as compared to the positive elements.Hence, identifying the factors that result in the customers’ dissatisfaction is vital. A total of 22 hotels with rating 2 and below on booking.com was analysed in the research. It was found that the dissatisfiers identified in the research are of these categories; room,hotel staff, services and environment. The findings show that the highest contributor to dissatisfaction is the “room”. This indicates that customers will be more satisfied if their hotel rooms are properly maintained. The poor rating hotel demand was also analysed. More results and important findings are discussed in the later section of this report. The results and findings of the research are useful to hotel operators in order to offer better services to customers.